Application of Norm Optimal Iterative Learning Control to Quadrotor Unmanned Aerial Vehicle for monitoring overhead power system - Foudeh, Husam A.; Luk, Patrick Chi-Kwong; Whidborne, James F. (MDPI, 2020)
Wind disturbances and noise severely affect Unmanned Aerial Vehicles (UAV) when monitoring and find in faults in overhead power lines. Accordingly, we propose repetitive learning as a new solution for the problem. In particular, the performance of Iterative Learning Control (ILC)that are based on optimal approaches are examined, namely (i) Gradient-based ILC and (ii) Norm Optimal ILC. When considering the repetitive nature of fault-findin tasks for electrical overhead power lines, this study develops, implements and evaluates optimal ILC algorithms for a UAV model.Moreover, we suggest attempting a learning gain variation on the standard optimal algorithms instead of heuristically selecting from the previous range. The results of both simulations and experiments o gradient-based norm optimal control reveal that the proposed ILC algorithm has not only contributed to good trajectory tracking, but also good convergence speed and the ability to cope with exogenous disturbances such as wind gusts.
Keywords: inspection task; power system; gradient-based ILC; NormOptimal ILC; Iterative Learning Control (ILC); quadrotor; unmanned aerial vehicles (UAVs)